Relationship between personality traits and organizational commitment: a case at Jabatan Kerja Raya, Batu Lintang, Kuching, Sarawak/ Nurul Shahera Ismail - Ismail, Nurul Shahera (2016)
The purpose of this present study is to examine the relationship between personality traits and organizational commitment among support staff in Jabatan Kerja Raya (JKR), Batu Lintang, Kuching, Sarawak. This present study used questionnaire for the purpose of data collection. There were 90 sets of questionnaire were sent to the respondents with the return rate 84.4% and only 76 of the respondents respond to that surveyed. After that, the data from questionnaire was analyzed using Statistical Science Software (SPSS) version 20. In order to determine whether there is relationship between personality traits and organizational commitment the researcher were used Pearson Correlation to test the relationship. The findings show the correlation value between variable (r=.847, p<0.01) which means that there is a significant relationship between personality traits and organizational commitment. Besides that, the researcher recommends that future research should expanded to the another company and location rather than Jabatan Kerja Raya, Batu Lintang, Kuching, Sarawak